High-Yielding Automated Convergent Synthesis of No-Carrier-Added [11C-Carbonyl]-Labeled Amino Acids Using the Strecker Reaction - Xing, Junhao; Brooks, Allen F.; Fink, Dylan; Zhang, Huibin; Piert, Morand R.; Scott, Peter J. H.; Shao, Xia (Synlett, 2017)
A new variant of the Strecker synthesis using no-carrier-added [11C]cyanide for the synthesis of radiolabeled amino acids is described. The protocol is fully automated using a radiochemistry synthesis module and applied to the production of a number of new PET radiotracers. [11C-Carbonyl]sarcosine, [11C-carbonyl]methionine, [11C-carbonyl]-N-phenylglycine, and [11C-carbonyl]glycine are all synthesized in moderate to good radiochemical yields. The synthesis of [11C-carbonyl]sarcosine has been validated for production of doses for clinical use, and preliminary evaluation of the new radiotracer in PC3 tumor-bearing mice is also reported.
Keywords: PET imaging; PET radiochemistry; carbon-11